(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT : With the increasing population and the activities of the community in the city of manado, also increased the amount of the more then the volume of trash in the produce. This is affecting the conditions of the LANDFILL at the moment. Waste management is the collection, transport, processing, recycling, or disposal of waste material. Waste management is very important in order not to bad on the community and the environment. The purpose of this study was to determine whether waste management by the cleanliness and Landscaping Manado city is already effective. Data collection techniques in research is through: direct observation to observation i.e location research, conduct interview and documentation. The research method used was qualitative research methods. The method of this research aims to know the effectiveness of waste management by the cleanliness and Landscaping of the city of Manado. As for who becomes the respondents in this study was the Secretary of the Department and staff officers of the Department of hygiene and Landscaping of the city of Manado and involving the community of the city of Manado. Based on the research that has been done then the effectiveness of waste management by cleanliness and Landscaping of the city of Manado city is still not effective because there are still many obstacles in the face. The government should give full attention towards waste management, especially in the area of detention that kecamatan bersehati market volume of trash. For it can be inferred that in the effectiveness of waste management in the service of cleanliness and Landscaping Manado was ineffective because of the criteria,namely production, efficiency,satisfaction, adaptation/customisation, developmentand no one is fulfilled. Key Words: Effectiveness, Waste Management